Renovación urbana en los barrios centro y García Rovira en el municipio de Bucaramanga, Santander. (2023)
The present design project began with the research conducted in various cities, as an input for the diagnosis of morphologies in urban centers. With the data plan formulated in the land use plan of Bucaramanga, the focus of this project is to recover at the urban level the selected intervention area of the downtown and Garcia Rovira neighborhoods of Bucaramanga's commune 15 (POT).